The FT-IR spectra of pyrazinamide complexes of transition metal(II) tetracyanonickelate - AKYÜZ, SEVİM (Elsevier, 2003)
M(PZA)2Ni(CN)4 {where M=Mn, Co, Fe, Ni or Cd; PZA=pyrazinamide} complexes have been prepared for the first time and their FT-IR spectra are reported in the 400–4000 cm−1 region. The spectral features suggest that the compounds are similar in structure to the Hofmann type two dimensional coordination polymer compounds, formed with Ni(CN)4−2 ions bridged by M(PZA)2+2 cations. PZA is coordinated to M(II) through the oxygen atom of the carbonyl group.
Keywords: Infrared spectra; Hofmann type complexes; Tetracyanonickelate; Transition metal; Pyrazinamide; Pyrazine carboxamide